2010
DOI: 10.1387/ijdb.082705fl
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid signalling is required for information transfer from mesoderm to neuroectoderm during gastrulation

Abstract: The hindbrain region of the vertebrate central nervous system (CNS) presents a complex regionalisation. It consists of 7-8 distinct morphological segments called rhombomeres, each with a unique identity provided by combinations of transcription factors. One class of signalling molecules, retinoids, have been shown to be crucial for hindbrain patterning through direct trans-activation of Hox genes in the neuroectoderm. However, how this morphogen acts is not yet fully understood. Here, we show that the retinoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…RA is required for hindbrain patterning (Muhr et al, 1999;Niederreither et al, 1999;Begemann et al, 2001;Sakai et al, 2001;Grandel et al, 2002;Kudoh et al, 2002;Emoto et al, 2005;Sirbu et al, 2005;Nordström et al, 2006;Lloret-Vilaspasa et al, 2010); yet, as our experiments show, posterior rhombomeres can develop independently of RA when the hindbrain territory is expanded caudally due to loss of Cdx4 (Fig. 6).…”
Section: Ra and Hindbrain Patterningmentioning
confidence: 49%
See 1 more Smart Citation
“…RA is required for hindbrain patterning (Muhr et al, 1999;Niederreither et al, 1999;Begemann et al, 2001;Sakai et al, 2001;Grandel et al, 2002;Kudoh et al, 2002;Emoto et al, 2005;Sirbu et al, 2005;Nordström et al, 2006;Lloret-Vilaspasa et al, 2010); yet, as our experiments show, posterior rhombomeres can develop independently of RA when the hindbrain territory is expanded caudally due to loss of Cdx4 (Fig. 6).…”
Section: Ra and Hindbrain Patterningmentioning
confidence: 49%
“…The alignment of neural and mesodermal tissues at the head-trunk transition requires their development to be coordinated. The present study provides evidence that RA is essential for the accurate alignment of the HB/SC transition to the craniovertebral junction (summarized in Table 1), and that this function is independent from the well-characterized function of RA in hindbrain patterning (Niederreither et al, 1997;Muhr et al, 1999;Begemann et al, 2001;Sakai et al, 2001;Grandel et al, 2002;Kudoh et al, 2002;Emoto et al, 2005;Sirbu et al, 2005;Nordström et al, 2006;Lloret-Vilaspasa et al, 2010). Specification of head and trunk territories in zebrafish is completed by mid to late gastrulation (Kim et al, 2002), shortly after prospective hindbrain cells become committed to their fate (Woo and Fraser, 1998) and prospective paraxial mesoderm cells ingress into the embryo, contributing to occipital and anterior vertebral somites (Muller et al, 1996).…”
Section: Ra Interacts With Fgf and Wnt Pathways To Regulate The Rostrmentioning
confidence: 60%
“…A recent study in frogs has convincingly shown that the blocking of RA signaling from mesoderm to neuroectoderm suppressed the expression of mid-axial hox genes in neurula embryos and led to distortion of segmental identity and reduction of posterior hindbrain (42). This prompted us to investigate whether the observed reduction of hoxd4 and the posterior hindbrain in rdhe2 morphants reflected a localized decrease in RA signaling.…”
Section: Expression Of Developmental Marker Genes Is Altered In Rdhe2mentioning
confidence: 98%
“…RARs function as ligand-modulated transcription factors that activate expression of their target genes (Chambon, 1996;Mangelsdorf et al, 1995;Mark et al, 2009). Studies in a variety of systems have shown that retinoic acid (RA) is an important component of the neural posteriorizing signal (Blumberg et al, 1997;Durston et al, 1989;Lloret-Vilaspasa et al, 2010;Papalopulu and Kintner, 1996;Shiotsugu et al, 2004) as well as of the AP patterning of the neural crest, somites and limbs (Moreno et al, 2008;Moreno and Kintner, 2004;Niederreither et al, 2002;Stratford et al, 1999;Villanueva et al, 2002). Retinoid signaling also establishes AP identity in the endoderm and mesoderm (Bayha et al, 2009;Deimling and Drysdale, 2009;Pan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%